Identification of a Disulfide Bridge Important for Transport Function of SNAT4 Neutral Amino Acid Transporter - Padmanabhan Iyer, Rugmani (Public Library of Science, 2013)
SNAT4 is a member of system N/A amino acid transport family that primarily expresses in liver and muscles and mediates the transport of L-alanine. However, little is known about the structure and function of the SNAT family of transporters. In this study, we showed a dose-dependent inhibition in transporter activity of SNAT4 with the treatment of reducing agents, dithiothreitol (DTT) and Tris(2-carboxyethyl)phosphine (TCEP), indicating the possible involvement of disulfide bridge(s). Mutation of residue Cys-232, and the two highly conserved residues Cys-249 and Cys-321, compromised the transport function of SNAT4. However, this reduction was not caused by the decrease of SNAT4 on the cell surface since the cysteine-null mutant generated by replacing all five cysteines with alanine was equally capable of being expressed on the cell surface as wild-type SNAT4. Interestingly, by retaining two cysteine residues, 249 and 321, a significant level of L-alanine uptake was restored, indicating the possible formation of disulfide bond between these two conserved residues. Biotinylation crosslinking of free thiol groups with MTSEA-biotin provided direct evidence for the existence of a disulfide bridge between Cys-249 and Cys-321. Moreover, in the presence of DTT or TCEP, transport activity of the mutant retaining Cys-249 and Cys-321 was reduced in a dose-dependent manner and this reduction is gradually recovered with increased concentration of H(2)O(2). Disruption of the disulfide bridge also decreased the transport of L-arginine, but to a lesser degree than that of L-alanine. Together, these results suggest that cysteine residues 249 and 321 form a disulfide bridge, which plays an important role in substrate transport but has no effect on trafficking of SNAT4 to the cell surface.